THE INFLUENCE OF DIRECT WRITTEN CORRECTIVE FEEDBACK TOWARD EFL STUDENTS’ ESSAY WRITING - Zia Hisni Mubarak; Alpino Susanto (English Study Program University of Pasir Pengaraian, 2018)
This research referred to the experiences of the researchers in providing students writing courses in the context of EFL (English as Foreign Language) in Batam. It was found that students’ essay writing contained several grammatical errors to plagiarism. This study aimed to determine the level of effectiveness of written corrective feedback (WCF) on the quality of students’ essay writing. The research method was quasiexperimental where the control class was given treatment by using no WCF and the experimental class was given WCF. Both scores from control and experiment classes were different. The mean of experiment class was higher than the mean from control class. After analyzing them statistically, it was found that the hypothesis (Ha) was accepted. It meant that WCF had a significant effect on the quality of essay writing. It was concluded that WCF is a better way in improving the quality of students' essay writing.